SENSORY ACCEPTANCE of JUICE FROM FCOJ PROCESSING STEPS - Janzantti, N. S. [UNESP]; Machado, T. V. [UNESP]; Monteiro, Magali [UNESP] (Wiley-Blackwell, 2011)
The acceptance of orange juice from the frozen concentrated orange juice (FCOJ) processing steps was evaluated by 101 consumers for color, overall impression, aroma, flavor and texture. The juice from the extraction, filtration, concentration, cooling and blend steps was collected at the beginning and the end of the 2009 harvest period. The juice from the extraction and filtration steps showed higher acceptance means for overall impression, aroma and flavor, while the juice from the concentration, cooling and blend steps had acceptance lower than the cutoff score. The internal preference mapping showed that color discriminated the juice from the collection periods while texture allowed discrimination between the steps of extraction and of filtration. The acceptance of the orange juice was driven by the aroma and flavor. The sensory acceptance was successfully applied to evaluate change during the process and the difference between the orange juice from different steps of the FCOJ processing.